A contrastive study of conceptual metaphors of “mother/ mẹ” in english and vietnamese 20th century songs - Lê Hoàng Ngân (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Make a contrastive analysis of conceptual metaphors of “Mother” / “Mẹ” in English and Vietnamese 20th century songs and then find out thes similarities and differences; Enable Vietnamese learners of English and English learners of Vietnamese to be more aware of the conceptual metaphor used in English and Vietnamese 20th century songs so that they could make use of conceptual metaphor in their own writing creatively and smoothly and make a considerable progress in their translation skill.